Functional Inflammatory Genotypes in Ischemic Stroke: Could We Use Them to Predict Age of Onset and Long-Term Outcome?. (29th April 2011) - Marousi, Stella; Antonacopoulou, Anna; Kalofonos, Haralambos; Papathanasopoulos, Panagiotis; Karakantza, Marina; Ellul, John
Abstract : Functional single-nucleotide polymorphisms (SNPs) of inflammatory cytokines have been previously related to the occurrence of an ischemic stroke (IS). We investigated whether five functional SNPs (i.e., TNF- α -308G>A, IL6-174G>C, IL12B 1188A>C, IL4-589C>T, and IL10-1082G>A) might be associated with the age of onset and 6-month outcome of an acute IS. A probe-free real-time PCR methodology was used to genotype 145 consecutively admitted cases with a first-ever IS. Simple Kaplan-Mayer and adjusted Cox regression analyses showed no association between inflammatory genotypes and the age of IS onset. IL6-174G>C, IL12B 1188A>C, IL4-589C>T, and IL10-1082G>A were not found to significantly contribute to the long-term outcome of the disease. However, carriage of the TNF- α -308 GG genotype was significantly associated with reduced odds for an adverse outcome. Larger studies are needed to confirm our results.